PEMBENTUKAN KARAKTER MURID PADA SDIT BUNAYYA PEKANBARU MELALUI PROGRAM MONITORING SEKOLAH - Yenni Yunita; Rojja Pebrian; Ismail Akzam (UIR PRESS, 2019)
SDIT Bunayya Pekanbaru is one of the schools that implements character education by applying the concept of Islamic education based on the Qur'an and Hadith, a school that integrates standard public-school curriculum with Islamic education. The purpose of this study was to determine student character education and the factors that influence student character education at the Integrated SDIT Bunayya Pekanbaru. This type of research is qualitative research. The subjects of this study were 45 teachers at SDIT Bunayya Pekanbaru. Data collection techniques in this study were observation, interviews, and documentation. The results showed that the formation of student character in SDIT Bunayya Pekanbaru is a school monitoring program that monitors about adab, prayer, study, read the Qur'an and repeat memorization by filling out student monitoring books. The factors that influence the formation of student character, namely the factors of parents, family, friends, the environment and electronic media such as the internet, mobile phones, gadgets, and TV shows.